Hemorrhoid Disease: A Review on Treatment, Clinical Research and Patent Data - Devi, Vishakha; Deswal, Geeta; Dass, Rameshwar; Chopra, Bhawna; Kriplani, Priyanka; Grewal, Ajmer S.; Dhingra, Ashwani K. (Infectious Disorders - Drug Targets, 2023)
Background: Hemorrhoid disease (HD) is an anal-rectal ailment that is commonly painful or may be painless and causes rectal bleeding with or without prolapsing anal tissue. It is generally associated with bleeding, prolapse, pruritus, and discomfort, which results in a diminished quality of life and well-being. Objective: To highlight the recent developments in terms of safety, clinical efficacy, and marketed formulation for the effective management of hemorrhoids. Method: Reported literature available on Scopus, PubMed, Science Direct, Clinicaltrails.gov, and from many reputed foundations has been studied to summarize the recent development and clinical studies for the management of hemorrhoids. Results and Conclusion: The high incidence of hemorrhoids obliges the development of new molecules; therefore, safe and efficient drugs to confer protection against hemorrhoids are urgently needed. This review article mainly focuses on the newer molecules to overcome hemorrhoids and also emphasizes various studies carried out in the past.
Keywords: hemorrhoids